Meiotic Silencing in Dothideomycetous Bipolaris maydis - Tsuji, Kenya; Kitade, Yuki; Yoshimi, Akira; Tanaka, Chihiro (Frontiers in Fungal Biology, 2022)
The filamentous ascomycete Bipolaris maydis is a plant pathogen that causes corn leaf blight and has been used in cytological studies of sexual reproduction. In this fungus, when null mutants of each septin are crossed with the wild-type strain, all ascospores derived from the same asci show abnormal morphology. The phenomenon was remarkably similar to the event known as “ascus dominance” in Neurospora crassa, which is known to be caused by MSUD (meiotic silencing by unpaired DNA). However, it is not clear whether B. maydis possesses functional MSUD. The object of this study is to elucidate whether this fungus carries a functional MSUD system that causes ascus dominance in the crosses of septin mutants and the wild-type strain. The results of homozygous and heterozygous crossing tests with mutants, having the insertional CDC10-septin gene sequence into the genome, suggested that the ascus dominance in B. maydis is triggered by the unpaired DNA as in N. crassa. To investigate whether MSUD is caused by the same mechanism as in N. crassa, an RNA-dependent RNA polymerase, one of the essential factors in MSUD, was identified and disrupted (Δrdr1) in B. maydis. When the Δrdr1 strain was crossed with each mutant of the septins, ascus dominance did not occur in all crosses. These results suggest that this ascus dominance is caused by RNA silencing triggered by an unpaired gene, as in N. crassa, and septin genes were affected by this silencing. To date, although MSUD has been found only in Fusarium graminearum and N. crassa, which are classified as Sordariomycetes, this study showed that MSUD is also functional in B. maydis, which is classified as a Dothideomycete. These results showed the possibility that this posttranscriptional regulation is extensively conserved among filamentous ascomycetes.